Anxiety Levels Among Pulmonary Tuberculosis Patients at Dr. Slamet General Hospital, Garut: A Descriptive Study - Yudi Muammar; Andri Nugraha; Muhammad Hadi Sulhan; Trisa Oktaviani (International Journal Of Health Science, 2025)
Pulmonary tuberculosis (TB) is a chronic infectious disease that not only imposes a significant physical health burden but also has profound psychological implications. Among the most commonly observed psychological responses in TB patients is anxiety, which can adversely affect their adherence to treatment regimens and hinder the overall recovery process. Anxiety may arise due to various factors such as prolonged illness, social stigma, isolation, fear of transmission, and uncertainty about treatment outcomes. This descriptive quantitative study aimed to assess the levels of anxiety experienced by pulmonary TB patients undergoing treatment at Dr. Slamet Hospital in Garut, Indonesia. A total of 77 participants who were actively receiving anti-tuberculosis therapy were recruited for the study. Data collection was conducted using the Indonesian version of the Depression Anxiety Stress Scales (DASS-42), a standardized instrument for measuring psychological distress. The findings revealed that a majority of the respondents experienced moderate levels of anxiety (37.7%). This was followed by severe anxiety in 23.4% of the patients, mild anxiety in 19.5%, extremely severe anxiety in 11.7%, and normal levels in only 7.7% of the participants. These results indicate that a considerable proportion of pulmonary TB patients are struggling with anxiety symptoms during their course of treatment. The study underscores the importance of integrating psychological support services into TB treatment programs. Addressing anxiety through counseling, mental health screening, and psychosocial interventions may enhance patients' emotional well-being, improve treatment adherence, and lead to more favorable clinical outcomes. Health professionals and policymakers are encouraged to recognize and respond to the mental health needs of TB patients to ensure a more holistic and effective care approach.